Preferences an office in commercial administration - Ali, Khalil ibrahim; Abood, Aday abas (Iraqi Journal of Architecture and Planning, 2009)
This speech resemble the Identity ofArchitecture. A task which makes busy the thinkers and educated class people in general and the Alchitectures in special, on a basic that the Identity resembles thoughts which are as a kind of eagemess and retuming back for the past till the point of resembling, as to be an expression for its role to achieve Identity this research deals with through two axis the first relate in describing the dimension and sides ofthe references in general sight and in Architecture in special sight. The research discusses the Architecture through explaining the linguistic and Idiomatic dimensions the philosophical side enlighten this reality and emerge discussions about the material and thoughts which are previously the better to limitate the research state from this discussion limited the state which indicates the complement of the two poles materials and thoughts giving less importance to thebestoneandneglectstheother.Theresearchshiftstotheotherexplanationofthis thought in the Architecture medial and what it means, what is related to it thrcugh the references which caused stress for the importance ofthe references role in architecture on one hand and explaining its kinds and branches depending on its relation to the field of Architecture and out side and referring to the differences according on it period or age and cercumestances which makes it to depend on the other hand what’s above has its importance in dehning the references and it differs from it in being a collective thought due to the tribally seen not having it collectively that means consisting the references in one of its sides due to what is previously not announcing the references in their collectively pictures the research indicates the role of references in achieving the Identity through depending on the association’ It means achieving a kind of connecting with the cultural and civilization heretic and the national roots in their in their indicates the importance of references and its necessity in achieving the Identity and indicating a smart and creative beheviour in the presence of references not meaning it to reduce it simportance to the hibal state or shifting it to the historical relations and become as ash through analyzing the reality of now a days Architecture. In addition to the explanation ofhow to behave with references in the frame of achieving the Architecture have Identity’